Community Empowerment Of RT 21, Sawah Lebar Baru Subdistrict Through Digital Literacy Training To Support Digital Transformation - Delon Hadi Winata; Bima Trisentyia; Iluh Frensia Paramita; Tiara Pia; Tutut Dwinka Utari; Dimas Aulia Trianggana (Jurnal Pengabdian Mandiri, 2026)
This study examines the implementation of a digital literacy training program for the community of RT 21, Sawah Lebar Baru Village, as an effort to enhance residents’ digital competencies in supporting digital transformation. The study aims to evaluate the program’s implementation, community participation, and its impact on improving participants’ digital literacy. A descriptive qualitative approach was used through interviews, observations, and documentation involving more than 60 participants per day who attended the training. The findings show that the six-day program received positive responses from the community, with an attendance rate of 88%. Training materials such as the use of digital devices, digital security, online communication, and the utilization of public service applications contributed to improving participants’ digital skills. Residents demonstrated increased understanding of basic technology use and the ability to independently access digital-based services. The study concludes that the program has been effective in enhancing digital literacy and technological awareness within the community, although challenges such as limited devices and variations in training materials need to be addressed to ensure its sustainability.